Communication—Enhancement of Structural Stability of LiNi0.5Co0.2Mn0.3O2 Cathode Particles against High-Voltage Cycling by Lithium Silicate Addition. Issue 6 (20th March 2019) - Kato, Yukihiro; Hashinokuchi, Michihiro; Hashigami, Satoshi; Yoshimi, Kei; Yoshida, Hiroyuki; Inagaki, Toru; Haruta, Masakazu; Doi, Takayuki; Inaba, Minoru
Abstract : Lithium silicate was incorporated within Ni0.5 Co0.2 Mn0.3 (OH)2 precursor particles via an anti-solvent precipitation method to prepare lithium silicate-added LiNi0.5 Co0.2 Mn0.3 O2 (NCM) particles. Lithium silicate was found at the grain boundaries in the NCM secondary particles, which significantly improved the capacity retention in high voltage operation (3.0–4.6 V). Cross-sectional SEM images revealed that cracks were seriously formed inside the lithium silicate-free NCM particles after cycling, while crack formation was remarkably inhibited for lithium silicate-added NCM. These results suggested that lithium silicate at the grain boundaries strengthened the interfacial-adhesion between primary particles, resulting in the improved cycling stability.